Transcriptomic Landscapes of Immune Response and Axonal Regeneration by Integrative Analysis of Molecular Pathways and Interactive Networks Post-sciatic Nerve Transection - Guo, Qi; Zhu, Hui; Wang, Hongkui; Zhang, Ping; Wang, Shengran; Sun, Zhichao; Li, Shiying; Xue, Chengbin; Gu, Xiaosong; Cui, Shusen (Frontiers in Neuroscience, 2018)
Potential interaction between immune response and axonal regeneration has recently attracted much attention in peripheral nervous system (PNS). Previously, global mRNA expression changes in proximal nerve segments were profiled and merely focused on the differentially change of the key biological processes. To further uncover molecular mechanisms of peripheral nerve regeneration, here we focused on the interaction between immune response and axonal regeneration that associated with specific molecular pathways and interactive networks following sciatic nerve transection. To offer an outline of the specific molecular pathways elaborating axonal regeneration and immune response, and to figure out the molecular interaction between immune response and axonal regeneration post-sciatic nerve transection, we carried out comprehensive approaches, including gene expression profiling plus multi-level bioinformatics analysis and then further experimental validation. Alcam, Nrp1, Nrp2, Rac1, Creb1, and Runx3 were firstly considered as the key or hub genes of the protein-protein interaction (PPI) network in rat models of sciatic nerve transection, which are highly correlated with immune response and axonal regeneration. Our work provide a new way to figure out molecular mechanism of peripheral nerve regeneration and valuable resources to figure out the molecular courses which outline neural injury-induced micro-environmental variation to discover novel therapeutic targets for axonal regeneration.